Pengaruh Pendekatan Tematik Terhadap Perkembangan Kognitif Anak - Nazli Ikhwani MZ; Armanila Armanila; Rizka Amalia (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
. The purpose of this study is to explain the cognitive development of group B children in Melati Kindergarten. It can be seen from some of the children's attitudes which are lacking, including showing that they cannot recognize differences based on size, sorting objects based on large to small sizes and vice versa, and presenting various kinds of objects in the form of picture or writing.This type of research is the Pre-Experimental Design used in this study is the Intac-Group Comparison. The population taken was only class B2, namely only one class and used the pre test and post test on 2 groups that were in one class. The sampling technique uses purposive sampling technique, namely determining the sample based on certain considerations, so that each member of the population does not have the same opportunity. Data collection using observation and documentation guidelines and technical data analysis using descriptive statistics and inferential statistics.The results of this study indicate a significant influence between thematic approaches and children's cognitive development. This can be seen from the average pre-test cognitive development of group B children who used a thematic approach, which was 43.4, while the post-test average score was 76.9. From these data, it was obtained an increase in the score of 33.5 after using a thematic approach.